PENGARUH PENDAPATAN ASLI DAERAH TERHADAP BELANJA MODAL DI PROVINSI RIAU - Hartiningsih, Nina; Halim, Edyanus Herman (Jurnal Tepak Manajemen Bisnis, 2015)
This study aimed to test the Regional Income Effect on Capital Expenditure in Riau Province.The analysis method used in this research is descriptive method with regression testing to test theclassical assumption prior to getting the best research model. The variable in this study is the RegionalTax, Regional Fees and Other Legal PAD as an independent variable and capital expenditures as thedependent variable. The population was Riau Provincial Government Budget Realization. Sampleresearch is Actual Budget 12 districts / cities in Riau Province in 2008 to 2012.These results prove that simultaneous local taxes; levies and other legal PAD effect on capitalexpenditure in Riau Province. In partial, local taxes and other legal PAD effect on capital expenditurein Riau Province. While local levies no effect on Capital Expenditure.Keywords: local taxes; levies; other PAD legitimate and capital expenditure.